Formulasi Kebijakan Pemindahan Lokasi Dinas Kelautan Dan Perikanan Kabupaten Lingga Di Kecamatan Senayang - Romy Subanu; Yusri Munaf (UIR Press, 2021)
The relocation of the Department of Marine Affairs and Fisheries of Lingga Regency to the Senayang Districtreceived the attention of the community, therefore it is interesting to review from a policy point of view. The purpose of this study was to understand the policy formulation of the relocation of the Department of Marine Affairs and Fisheries ofLingga Regency to Senayang District from the point of view of a goal-oriented model. The type of research selected is qualitative- descriptive. The location of this research is the Department of Marine Affairs and Fisheries of Lingga Regency, which at this time has changed the nomenclature to the Department of Fisheries of Lingga Regency Service.Informants were selected purposively and snowball sampling. Primary data is obtained directly from informants through interviews and secondary data comes from related documents. The results showed that the policy formulation for relocating the Department of Marine Affairs and Fisheries of Lingga Regency to the Senayang District did not support resource management to achieve the goal because most of the resources were not available. In addition, the goal to be achieved – namely providing easy access and services to fishing communities in Senayang District – does not meet thecriteria as a good goal.